11C‐Metomidate PET/CT is a useful adjunct for lateralization of primary aldosteronism in routine clinical practice. (18th March 2019) - O'Shea, Paula M.; O'Donoghue, Darragh; Bashari, Waiel; Senanayake, Russell; Joyce, Mary B.; Powlson, Andrew S.; Browne, Darragh; O'Sullivan, Gerard J.; Cheow, Heok; Mendichovszky, Iosif; Quill, Denis; Lowery, Aoife; et al.
Summary: Objective: To describe clinical practice experience of 11 C‐Metomidate PET/CT as an adjunct to adrenal vein sampling (AVS) in the lateralization of aldosterone‐producing adenomas (APA) in primary aldosteronism (PA). Context: Accurate lateralization of APA in the setting of PA offers the potential for surgical cure and improved long‐term cardiovascular outcomes. Challenges associated with AVS, the current gold standard lateralization modality, mean that only a small proportion of potentially eligible patients currently make it through to surgery. This has prompted consideration of alternative strategies for lateralization, including the application of novel molecular PET tracers such as 11 C‐Metomidate. Design: Clinical Service Evaluation/Retrospective audit. Patients: Fifteen individuals with a confirmed diagnosis of PA, undergoing lateralization with 11 C‐Metomidate PET/CT prior to final clinical decision on surgical vs medical management. Measurements: All patients underwent screening aldosterone renin ratio (ARR), followed by confirmatory testing with the seated saline infusion test, according to Endocrine Society Clinical Practice Guidelines. Adrenal glands were imaged using dedicated adrenal CT. 11 C‐Metomidate PET/CT was undertaken due to equivocal or failed AVS. Management outcomes were assessed by longitudinal measurement of blood pressure, ARR, number of hypertensive medications following adrenalectomy or institution of medical therapy. Results: We describe the individual lateralization and clinical outcomes for 15 patients with PA. Conclusion: 11 C‐Metomidate PET/CT in conjunction with adrenal CT and AVS provided useful information which aided clinical decision‐making for PA within a multidisciplinary hypertension clinic.